Does Improving Financial Literacy Enhance Small and Medium-Size Enterprise Performance? - Dwi Novita Sari; Hardianawati, Hardianawati (International Journal of Applied Economics, Accounting and Management (IJAEAM), 2023)
Financial literacy research in small and medium-sized firms (SMEs) has sparked considerable interest in recent years, evolving both swiftly and unevenly. Through a bibliometric analysis and a systematic literature evaluation, this research is the first to give a credible, consistent, and up-to-date overview of financial literacy in SMEs. After identifying the most influential agents involved in this field of research, we conducted a co-occurrence analysis of the authors' keywords, a co-citation analysis of the cited references, and an in-depth analysis of 50 documents published between 2017 and 2023. According to the findings, SME financial literacy research has largely focused on the following topics: (1) performance, (2) access to financing, (3) innovation, (4) risk mentality and entrepreneurship, (5) owners-managers, and residual contributions. This research structure is supported by the following theoretical foundations: (1) the resource-based view, (2) pecking order theory, agency theory, and trade-off theory, (3) the entrepreneurial orientation viewpoint, human capital theory, and upper echelon theory, and (4) planned behavior theory. Following that, we created an integrated framework on which to base ideas for major future research directions. As a result, this study provides a detailed and comprehensive overview of this new research topic